Pelatihan Pengumpulan Data Menggunakan Platform KoboToolbox Pada Mahasiswa Administrasi Kesehatan Fakultas Ilmu Keolahragaan Dan Kesehatan - Fitri, A. Ulfiana; Handayani, Meliana; Kas, Sri Rezkiani; Samsiana, Samsiana; Haeril, Haeril (Universitas PGRI Semarang, 2025)
Digital data collection skills have become essential for students in the field of health administration. KoboToolbox is an open-source platform that offers ease in creating survey forms as well as collecting and managing data, both online and offline. This community service activity aimed to introduce and train students from the Health Administration program of the Faculty of Sports and Health Sciences in the use of KoboToolbox. The methods used included theoretical socialization, direct platform demonstration, independent practice by participants, and evaluation of understanding through pre-test and post-test assessments. This activity was enthusiastically attended by 254 students. Evaluation results showed an increase in the average score from 45.0 in the pre-test to 83.6 in the post-test, reflecting a 38.6-point improvement. This improvement indicates the effectiveness of the socialization and hands-on practice approach in enhancing participants' digital literacy, particularly in the context of health data collection. Challenges encountered included internet connectivity issues and initial adaptation to the platform interface, which were overcome through intensive guidance. It is expected that the skills gained from this activity can be applied in academic work, research, and field practices in the future, and serve as a crucial asset to support technology-based health information systems.